Stratum Corneum Lipids: Their Role for the Skin Barrier Function in Healthy Subjects and Atopic Dermatitis Patients - van Smeden, Jeroen; Bouwstra, Joke A (Current problems in dermatology, 2016)
Human skin acts as a primary barrier between the body and its environment. Crucial for this skin barrier function is the lipid matrix in the outermost layer of the skin, the stratum corneum (SC). Two of its functions are (1) to prevent excessive water loss through the epidermis and (2) to avoid that compounds from the environment permeate into the viable epidermal and dermal layers and thereby provoke an immune response. The composition of the SC lipid matrix is dominated by three lipid classes: cholesterol, free fatty acids and ceramides. These lipids adopt a highly ordered, 3-dimensional structure of stacked densely packed lipid layers (lipid lamellae): the lateral and lamellar lipid organization. The way in which these lipids are ordered depends on the composition of the lipids. One very common skin disease in which the SC lipid barrier is affected is atopic dermatitis (AD). This review addresses the SC lipid composition and organization in healthy skin, and elaborates on how these parameters are changed in lesional and nonlesional skin of AD patients. Concerning the lipid composition, the changes in the three main lipid classes and the importance of the carbon chain lengths of the lipids are discussed. In addition, this review addresses how these changes in lipid composition induce changes in lipid organization and subsequently correlate with an impaired skin barrier function in both lesional and nonlesional skin of these patients. Furthermore, the effect of filaggrin and mutations in the filaggrin gene on the SC lipid composition is critically discussed. Also, the breakdown products of filaggrin, the natural moisturizing factor molecules and its relation to SC-pH is described. Finally, the paper discusses some major changes in epidermal lipid biosynthesis in patients with AD and other related skin diseases, and how inflammation has a deteriorating effect on the SC lipids and SC biosynthesis. The review ends with perspectives on future studies in relation to other skin diseases.